2003
DOI: 10.1021/cg0340493
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Crystal Growth and Morphology Control of Benzopinacol Produced from Benzophenone in Ethanol/Water Mixed Solution

Abstract: Laser-induced precipitation and crystal growth were observed by an irradiation of benzophenone in an ethanol and water mixed solvent. The crystal was composed of benzopinacol produced from excited benzophenone through a benzophenone ketyl radical. Polyhedral, skeletal, and dendrite morphologies of benzopinacol were controlled by laser energy. This is the first example of a photochemical morphology control of a crystal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 11 publications
0
55
0
Order By: Relevance
“…They conjectured that the optical Kerr effect aligned the molecules within urea and glycine clusters, leading to the nucleation. Okutsu and co-workers [6][7][8][9][10][11] also demonstrated light-induced nucleation by a photochemical method. Irradiation by ultraviolet (UV) light produced radicals of aromatic compounds, which could act as nucleation sites for crystallization.…”
Section: Introductionmentioning
confidence: 94%
“…They conjectured that the optical Kerr effect aligned the molecules within urea and glycine clusters, leading to the nucleation. Okutsu and co-workers [6][7][8][9][10][11] also demonstrated light-induced nucleation by a photochemical method. Irradiation by ultraviolet (UV) light produced radicals of aromatic compounds, which could act as nucleation sites for crystallization.…”
Section: Introductionmentioning
confidence: 94%
“…To date, light-induced nucleation has been demonstrated by optical Kerr effect [1][2][3][4][5][6][7][8], photon pressure [9,10], and photochemical reactions [11][12][13][14][15][16]. As another approach, we have proposed the focused irradiation of a femtosecond laser [17][18][19][20][21][22][23][24], whose peak intensity is $TW/cm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…To date, an increasing number of studies have demonstrated lightinduced nucleation by photo-physical 1-5 and chemical [6][7][8] methods. A femtosecond laser ͑peak intensity ϳgigawatts͒ is one of the promising techniques to induce nucleation at low supersaturation, which will improve crystal quality.…”
mentioning
confidence: 99%